Digitization of virtual reality-based ethnomathematics learning to improve students ' mathematical critical thinking in geometry courses - Fikri Apriyono (International Journal on Teaching and Learning Mathematics, 2025)
This study explored the development and effects of a Virtual Reality-based ethnomathematics learning medium aimed at enhancing students' mathematical critical thinking skills in analytic geometry. The study addressed the challenges students encounter in visualizing three-dimensional concepts. A development framework was implemented in conjunction with a quasi-experimental design involving mathematics education students at UIN KHAS Jember during the 2023/2024 academic year. The learning media were validated by nine experts in content, media, and instructional design, and underwent usability testing with 21 student participants. Quantitative data were gathered from pretest and posttest assessments and analyzed to determine the magnitude of learning gains. The experimental group achieved an average N-Gain score of 0.68, classified as moderate improvement, while the control group attained an N-Gain of 0.61. Qualitative data from classroom observations and open-ended questionnaires provided additional insight into user experience. The results showed that the VR-based tool significantly enhanced students’ mathematical critical thinking and was positively rated for usability, navigation, and engagement. Students also appreciated the integration of cultural elements, which enriched their conceptual understanding. These findings emphasize the potential of immersive and culturally responsive learning environments for STEM education. The study recommended broader implementation of such tools and suggested further research on scalability and long-term cognitive impacts.